Hubungan Pola Asuh Orangtua dan Komunikasi Interpersonal dengan Perilaku Seksual Pranikah Remaja di SMK Prestasi Agung Jakarta - Rina veronica; Ade ubaidah; Margaretha Lelyana (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Premarital sexual behavior of adolescents is a problem that often occurs today, because it can cause various negative impacts. The relationship between adolescent parents has both direct and indirect influences on adolescent premarital sexual behavior. Openness between parents and teenagers is important in order to avoid negative influences that exist outside the family environment. The purpose of this study was to determine the relationship between Parenting Paterns and Interpersonal Communication with Premarital Sexual Behavior of Adolescents at SMK Prestasi Agung, Jakarta. The design of this study used a cross sectional design with a quantitative approach. The population and research sample were 66 respondents. The analytical application used was SPSS 22. The results of the study H0: accepted and H1: rejected, r = 0.035 < 0.05 indicating there is a relationship between parenting patterns and adolescent premarital sexual behavior, while r = 0.154> 0.05 indicates there is no relationship between interpersonal communication and adolescent premarital sexual behavior